2022
DOI: 10.1088/1742-6596/2265/2/022033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the thrust force induced by wind turbine rotors on the incoming wind field: A wind LiDAR experiment

Abstract: A field experiment was conducted to investigate the effects of the thrust force induced by utility-scale wind turbines on the incoming wind field. Five wind profiling LiDARs and a scanning Doppler pulsed wind LiDAR were deployed in the proximity of a row of four wind turbines located over relatively flat terrain, both before and after the construction of the wind farm. The analysis of the LiDAR data collected during the pre-construction phase enables quantifying the wind map of the site, which is then leverage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…However, Bleeg et al 22 did not take into account the stability of the atmospheric flow. In a recent field experiment performed with wind scanning LiDARs, 23 it was found that the velocity reduction upwind of a wind turbine varied depending on the atmospheric stratification.…”
Section: Introductionmentioning
confidence: 99%
“…However, Bleeg et al 22 did not take into account the stability of the atmospheric flow. In a recent field experiment performed with wind scanning LiDARs, 23 it was found that the velocity reduction upwind of a wind turbine varied depending on the atmospheric stratification.…”
Section: Introductionmentioning
confidence: 99%
“…Several scanning technologies and strategies have been adopted to probe the atmospheric boundary layer for wind energy applications. Profiling lidars have been deployed for freestream resource assessment (Gottschall et al, 2012;Optis et al, 2021;Sharma et al, 2021), wake characterization (Heisel et al, 2018) and plant induction quantification (Jacquet et al, 2022;Letizia et al, 2022). Scanning lidars, i.e., those that feature the ability to direct the laser beam in arbitrary directions (among other abilties), offer additional flexibility and permit a more targeted characterization of the wind plant flow.…”
Section: Introductionmentioning
confidence: 99%